Nafion Coated Mg50Ni50 and (La,Mg)2Ni7 Negative Electrodes for NiMH Batteries - Eyövge, Cavit; Öztürk, Tayfur (Journal of the Electrochemical Society, 2018)
A study is carried out to develop a surface modified Mg based alloy with an improved discharge capacity that would be durable in alkaline environment. For this purpose, Mg50Ni50 alloy is synthesized via ball milling of elemental powders and tested electrochemically in both bare and nafion coated form. The study shows that the bare electrode yields an acceptable discharge capacity but subject to a fast capacity decay. Nafion coating is effective in reducing the capacity decay where the discharge capacity after 20 cycle is as high as 82% of the initial capacity. The study further shows that there is a substantial increase in the discharge capacity of the electrode with nafion coating. This is also investigated with a more traditional alloy of (La0.70Mg0.30)2(Ni0.85Co0.15)7. The capacities which are 329 and 334 mAh/g in bare electrodes, in the first cycle, are increased to 498 and 448 mAh/g with nafion coating for Mg50Ni50 and La0.70Mg0.30)2(Ni0.85Co0.15)7 respectively. It is proposed that the increase in discharge capacity is due to the increase in local hydrogen pressure at electrode-nafion interface made possible by the nafion envelope resulting in the increased hydrogen storage in the active powders.